INSULIN AND INSULIN RESISTANCE: NEW MOLECULE MARKERS AND TARGET MOLECULE FOR THE DIAGNOSIS AND THERAPY OF DISEASES OF THE CENTRAL NERVOUS SYSTEM - A. B. Salmina; N. A. Yauzina; N. V. Kuvacheva; M. M. Petrova; T. Ye. Taranushenko; N. A. Malinovskaya; O. L. Lopatina; A. V. Morgun; Ye. A. Pozhilenkova; O. S. Okuneva; G. A. Morozova; S. V. Prokopenko (Бюллетень сибирской медицины)
The review summarizes current data on the role of insulin in the regulation of t glucose metabolism in the central nervous system at physiologic and pathologic conditions. For many years, the brain has been considered as an insulin-independent organ which utilizes glucose without insulin activity. However, it is become clear now that insulin not only regulates glucose transport and metabolism, but also has modulatory efftects in impact on excitability, proliferation and differentiation of brain progenitor cells, synaptic plasticity and memory formation, secretion of neurotransmitters, apoptosis. We have critically reviewed literature information and our own data on the role of insulin and insulin resistance in neuron-glia metabolic coupling, regulation of NAD+ metabolism and action of NAdependent enzymes, neurogenesis, brain development in (patho)physiological conditions. The paper clarifies interrelations between alterations in glucose homeostasis, development of insulin resistance and development of neurodegeneration (Alzheimer's disease and Parkinson's disease), autism, stroke, and depression. We discuss the application of novel molecular markers of insulin resistance (adipokines, α-hydroxybutyrate, BDNF, insulin-regulated aminopeptidase, provasopressin) and molecular targets for diagnostics and treatment of brain disorders associated with insulin resistance.